Teluk Latak Village Information System, Bengkalis District, Bengkalis Regency Through Aerial Mapping: Sistem Informasi Desa Teluk Latak Kecamatan Bengkalis Kabupaten Bengkalis Melalui Pemetaan Udara - Reni Suryanita; Yohannes Firzal; Benny Hamdi Rhoma; Yenita Roza; Harnedi Maizir (Universitas Lancang Kuning, 2023)
Teluk Latak Village is located in Bengkalis District, Bengkalis Regency, Riau. It has 2 hamlets, namely Langgam Muara Hamlet and Simpang Baru Hamlet. Teluk Latak Village is one of the coastal villages in the west of Bengkalis Island which has a flat topography with an area of ​​​​approximately 23 km2. The problem that arises in Teluk Latak Village is that the regional potential of the natural resources in the area has not been explored. To obtain information on the geographical and geological conditions of Teluk Latak Village, aerial mapping is necessary. Therefore, the purpose of this community service activity is to utilize geospatial data through aerial mapping in Teluk Latak Village, Bengkalis District, Bengkalis Regency, Riau. The method of implementation is to conduct aerial mapping using drone equipment to obtain land and vegetation conditions in the Teluk Latak village area. It is hoped that this activity can contribute to village residents and village officials in mapping the potential of Teluk Latak Village in the social and economic fields.